Tinjauan Pelaksanaan Pengawasan Sistem Penjajaran Rekam Medis Sesuai Prosedur Di Rumah Sakit Islam Jakarta Cempaka Putih Jakarta Pusat - Muhammad Hafiz Zuhri; Yati Maryati; Lily Widjaya; Puteri Fannya (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Medical record is a document that contains patient identity data, treatment, examination, action, and other services that have been given to patients. In order for medical records to be maintained, supervision is needed in medical records. The purpose of this study was to find out how the oversight of the medical record alignment system with the Standard Operating Procedures at the Jakarta Islamic Hospital Cempaka Putih. This research method uses a descriptive method with qualitative analysis, conducting observations and interviews that aim to provide an overview and see directly a state of the supervision process during the alignment of medical records in the filing room of the Jakarta Islamic Hospital Cempaka Putih. This research was conducted in a storage room with 5 informants. The results of the study showed that the supervisory process was aligned with the supervisory element, namely determining the size of the implementation, there was a deficiency, namely there was no mention of tasks in the job description in controlling medical records. In measuring the actual implementation, there are inappropriate implementations such as misfiles and there are several tracers that are still hanging. In measuring behavior, officers do not yet have definite standards or tools to measure officer performance behavior. Obstacles in the alignment of medical records through the 5M factor, namely, the lack of number of officers in the filing room, the occurrence of misfiles and staff errors in writing unclear numbers. Materials namely, there are a lot of maps that are too thick. Machines, that is, there are still many tracers hanging on storage racks whose time limit has passed the stipulation. Methods, that is, the Hospital does not yet have an SOP for alignment supervision and there is only a Medical Record alignment system in the SOP for storing and returning Medical Records.